2010
DOI: 10.5014/ajot.2010.64s57
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy’s Perspective on the Use of Environments and Contexts to Support Health and Participation in Occupations

Abstract: PurposeThis paper articulates the position of the American Occupational Therapy Association (AOTA) regarding how, across all areas of practice, occupational therapy practitioners 1 select, create, and use environments and contexts to support clients' health and participation in desired occupations. IntroductionThe value and purpose of occupational therapy is to support the health and participation of clients by engaging them in their desired occupations (AOTA, 2008). Occupations are activities that "reflect cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Occupational therapy is a profession that considers the transactional relationship between the person and the environment or context and this affects the engagement in occupationsthese contexts may range from the physical, social, cultural and even virtual (American Occupational Therapy Association, 2014; Cohn & Lew, 2010;Cole & Tufano, 2008). Moreover, recent events put forth a need for occupational therapists to ensure engagement despite the occupational disruption caused by COVID-19 (Hammell, 2020).…”
Section: Reason For New Practice and The Role Of Occupational Therapymentioning
confidence: 99%
“…Occupational therapy is a profession that considers the transactional relationship between the person and the environment or context and this affects the engagement in occupationsthese contexts may range from the physical, social, cultural and even virtual (American Occupational Therapy Association, 2014; Cohn & Lew, 2010;Cole & Tufano, 2008). Moreover, recent events put forth a need for occupational therapists to ensure engagement despite the occupational disruption caused by COVID-19 (Hammell, 2020).…”
Section: Reason For New Practice and The Role Of Occupational Therapymentioning
confidence: 99%
“…Engagement and participation in occupation take place within the social and physical environment situated within context ( American Occupational Therapy Association, 2010 ) and serve as an important resource for physical and psychosocial well-being, given that they offer opportunities for physical activity as well as a restorative space for people living in urban environments ( Hartig et al, 2014 ; Wood et al, 2018 ). Schipperjin et al (2017) found that living in a neighbourhood with more parks within 1 km of one’s home was associated with greater leisure-time physical activity.…”
Section: Introductionmentioning
confidence: 99%